Deformation characteristics and cumulative plastic strain prediction model of saturated silty filler under intermittent heavy-haul train loads - Rusong Nie; Yongchang Tan; Zurun Yue; Weidong Wang; Fan Mo (European Journal of Environmental and Civil Engineering, 2026)

Genesis of high-grade uranium mineralization in sandstone-hosted uranium deposits in the northern Sichuan Basin - Zongbo Zhang; Zhengqi Xu; Minghui Yin; Qiwei Feng; Banghong Mo; Qiushuang Fan; Peng Ning; Taosheng Sun; Jincheng He (Ore and Energy Resource Geology, 2026)

Effects of different morphologies of CeOₓ on the unsaturated Mn/Co defects of MnOₓ/CoOₓ catalysts for highly active photothermocatalysis of acetone and NO - Siqi Jiang; Sihan Li; Yinming Fan; Yanping Zhang; Shengpeng Mo; Lei Liao; Yanan Zhang; Xiaobin Zhou; Zongqiang Zhu (Journal of Environmental Chemical Engineering, 2026)

Fulvic acid regulates ferrihydrite-to-hematite transformation and its redistribution under controlled abiotic aging conditions - Wei Yu; Zhengcong Geng; Jingyuan Dai; Zixin Zhang; Kaixuan Wang; Chenxi Zhang; Fan Mo; Xiaoming Zhao; Haibo Li (Journal of Environmental Chemical Engineering, 2026)

The SlDREBA4-SlASIL2 module mediates tomato thermotolerance by regulating the expression of SlHSP20/90 - Xinyun Li; Haoran Zhang; Yunrong Mo; Yu Liu; Yuhao Jing; Kaiyun Chen; Ying Zhou; Zushuai Ma; Wei Fan; Junqiang Xu; Kai Zhao; Yanyan Wang (Theoretical and Applied Genetics, 2026)

Gut Microbiota from Patients with Long COVID Persisting for 2 Years Result in Alterations in Mice that Resemble Post-COVID Symptoms - Daya Zhang; Chen Chen; Yunqian Xie; Shuo Zhou; Da Li; Fan Zeng; Shimei Huang; Yanting Lv; Xianfeng Huang; Fengjiao Mao; Runyu Chen; Ying Mo; et al. (Probiotics and Antimicrobial Proteins, 2026)

The plastic-carbon-climate nexus: Carbon sequestration, microbial adaptation, and land use solutions for a warming microplastics-contaminated world - Zelin Hou; Fan Mo; Yongkang Wu; Yin Lu; Qixing Zhou; Dawen Gao (Critical Reviews in Environmental Science and Technology, 2026)

Taurine attenuates heat stress-induced intestinal permeability by inhibiting endoplasmic reticulum stress and modulating gut microbiota - Haoran Jiang; Fan Mo; Zhuobin Pan; Chong Wang; Yanjun Cui (Journal of Thermal Biology, 2026)

Enhanced stability of goji berry chromoplasts through ultrasonication and high-pressure homogenization for carotenoid delivery - Xilong Li; Nan Chen; Fan Wu; Jingyu Gao; Mo Li; Yuanying Ni; Xin Wen (Food Bioscience, 2026)

Lactiplantibacillus plantarum SP055 pretreatment attenuates experimental colitis in association with partial preservation of epithelial integrity and microbial-metabolic homeostasis - Jianwei Zang; Xiaotong Hao; Yibo Shi; Xia Fan; Yimeng Kou; Xiaogan Zhao; Qiaoya Mo; Di Yu; Jiamin Xu; Chunling Meng; Chang Xu; Luyao Xiao; et al. (Food Bioscience, 2026)

Dietary Bacillus velezensis FL9 enhances growth, intestinal health and Aeromonas hydrophila resistance in Cyprinus carpio - Huixiang Li; Binhua Mo; Yue Luo; Wanqi Wang; Lanfen Fan (Fish & Shellfish Immunology, 2026)

Fulvic acid loading controls the retention-mineral stabilization trade-off of arsenate during oxic ferrihydrite aging - Wei Yu; Fan Mo; Jingyuan Dai; Chenxi Zhang; Kaixuan Wang; Ting Ma; Haishen Jiang; Xi Chen; Xiaoming Zhao; Haibo Li (Chemical Engineering Journal, 2026)

Identifying RNA ac4C Modification Sites via Pseudo-Nucleotide Fingerprint Encoding and Multi-Scale Feature Integration - Yiming Wang; Fan Mo; Yun Sha; Zhenguo Wen; Chun Fang (Interdisciplinary Sciences: Computational Life Sciences, 2026)

Tuning the thermal reactivity of low-rank coal: The structural role of phenolic hydroxyl groups from molecular aggregation to pore collapse - Hao Xu; Jin-Xi Wu; Yu-Hong Kang; Xing Fan; Ya-Ya Ma; Guang-Hui Liu; Ran-Ran Hou; Zhong-Qiu Liu; Wen-Long Mo; Yao Lu (Fuel, 2026)

Composition characteristics of the distillation waste residue from coal gasification crude phenol and pyrolysis product distribution of the corresponding residue - Jing Zhou; Bao-Kun Shi; Qing-He Ma; Ya-Ya Ma; Jie Yuan; Wen-Long Mo; Feng-Jun Ding; Bing Hu; Xing Fan; Xian-Yong Wei; Hai-Bao Huang (Fuel, 2026)

Analysis of microbiome succession and metabolome dynamics in Jiupei during Chinese strong-flavor Baijiu fermentation - Haiyan Xu; Weiping Kong; Qinglan Tang; Kequan Fan; Menghua Liu; Kai Mo; Zhancheng Xu; Wenxue Zhang (Food Research International, 2026)

Lipid-driven modulation of milk/soy proteins digestion in young child formulas: From in vitro gastric emptying to intestinal absorption coupled with in vivo protease activation - Qiaoya Mo; Jiahui Wang; Chang Xu; Xia Fan; Tao Lin; Kai Ma; Changliang Zhang; Shuo Geng; Feng Ji; Xin Rui; Wei Li (Food Research International, 2026)

Highly sensitive H2O2 colorimetric sensing in tumor cells via stable phospholipid-coated CsCu2I3 peroxidase-like nanoenzyme - Jiatong Wang; Yang Yu; Yawen Fan; Sihan Chen; Meiyi Mo; Shuo Yang; Yangyang Zhao; Zixu Zhang; Hongxian Han (Analytica Chimica Acta, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Click bubbles-driven enzyme-linked immunosorbent assay for enhanced biomarkers detection - Weifeng Liu; Xifeng Mo; Binqi Wei; Yuyuan Zhang; Yuanhang Xiang; Hao Lu; Haichao Li; Xiaojie Qin; Zhanyu Xu; Jie Yang; Fan Yang (Chemical Engineering Journal, 2026)

Biocontrol action of Cladosporium anthropophilum against the wheat powdery mildew fungus Blumeria graminis f. sp. tritici - Sujing Zhao; Ziyi Fan; Juncong Liu; Mo Zhu; Zongbo Qiu (BioControl, 2026)

Heatwaves intensify microplastic-driven greenhouse gas emissions from soil by modulating microbial abundance - Jianling Wang; Weitao Liu; Aurang Zeb; Qi Wang; Fan Mo; Ruiying Shi; Xinwei Shi; Yuexing Zhao; Chuan Yin; Yuebing Sun; Qixing Zhou (Journal of Cleaner Production, 2026)

Synergistic modification of β-casein micelles by dextran and genipin for naringenin delivery: A systematic evaluation of physicochemical stability, digestive properities, and cellular uptake - Jingying Ye; Fan Wu; Boran Yang; Zhaoyue Zhang; Xin Wen; Yuanying Ni; Mo Li (Food Bioscience, 2026)

An interpretable ensemble machine learning model for predicting carbon dioxide adsorption on magnesium oxide-based sorbents - Lin Fan; Yan He; Yunfeng Mo; Yiming Cao (Environmental Research, 2026)

The colonization, succession and ecological processes of saxicolous moss crust in the Qinling Mountains - Chun Wang; Jin Fan; Heming Wang; Qiuxia Mo; Xiangzhou Chen; Wenjuan Zhou; Chongfeng Bu; Yongsheng Xie (CATENA, 2026)

A novel TaqMan-based RT-qPCR assay for the detection of PEDV and discrimination of the G2c subtype - Yicong Fan; Xiang Li; Jiawen Mo; Liang Weng; Shiyu Liu; Xu Song; Rongli Guo; Wei Wang; Mi Hu; Shanshan Yang; Yongxiang Zhao; Baochao Fan; et al. (Archives of Virology, 2026)

A novel UV-assisted modification for fabricating wrinkled ligninsulfonate nanofiltration membranes with high flux and antibacterial properties - Guizhen Feng; Kailin Mo; Zhicheng Cui; Chaoran Fan; Yuntao Zou; Ju Rao; Zunquan Huang (Journal of Cleaner Production, 2026)

Morphology-dependent biotoxic effects and cellular damage mechanisms of silver nanoparticles on Chlorella vulgaris and Scenedesmus obliquus - Wei Yu; Yongchang Shang; Zhenyu Wang; Yue Yang; Chenxi Zhang; Ningcan Deng; Kaixuan Wang; Ting Ma; Xiuzhen Yang; Miao Xu; Fan Mo; Haibo Li (Algal Research, 2026)

Nonlinear dynamic surface-based event-triggered control for path-following and collision avoidance of unmanned sailboats with output constraints - Guangshi Xue; Zhipeng Shen; Weichao Mo; Yunsheng Fan; Haomiao Yu (Ocean Engineering, 2026)

PlantscRNAdb 4.0: Improved marker identification and annotation under a cell-type uniformity for plants - Dihuai Zheng; Xiaolin Lu; Yaqian Lu; Pu Liang; Nianmin Shang; Jiwei Xu; Jie Yao; Fangyu Mo; Qinjie Chu; Longjiang Fan; Hongyu Chen (Molecular Plant, 2026)

Effective separation of organic species from a shale oil sludge - He-Qi Liu; Xian-Yong Wei; Zhi-Hao Ma; Jing Chen; Xiao-Yan He; Zhi-Min Zong; Xing Fan; Yu-Hong Kang; Fang-Jing Liu; Hai-Xu Zou; Guang-Hui Liu; Yierxiati Dilixiati; et al. (Journal of Environmental Management, 2026)

Effects of microwave-stabilized rice aleurone layer flour (MSF) on gel properties of early-indica rice flour and semi-dried rice noodles in non-extruded and extruded systems - Yakun Song; Qing Wang; Weiling Mo; Chunmin Guan; Fan Qiao; Jianhua Zhu; Wenhua Zhou; Qinlu Lin; Chun Liu (Journal of Cereal Science, 2026)

Highly thermally stable catalysts for VOCs oxidation: Synthesis, characterization and mechanisms - Yuchuan Ye; Jinhu Wang; Xinxin Zhang; Huisheng Fan; Hui Wang; Liuye Mo; Lei Jiao (Fuel, 2026)

Long-term Nitrogen Addition Did Not Aggravate Soil Microbial Phosphorus Demand in a Tropical Forest - Xuehua Hu; Yubiao Lin; Qifeng Mo; Yingxu Fan; Faming Wang; Xiangping Tan; Qian Zhao (Journal of Soil Science and Plant Nutrition, 2026)

Improved drying performance and mass transfer in ginger slices using hot air-assisted radio frequency technique - Zijun Mo; Mengge Li; Jinsong Zhang; Liumin Fan; Rui Li; Shaojin Wang (Journal of Food Engineering, 2026)

Synergistic enhancement of CO2 capture via a dual-activator strategy: Mechanism insights into tertiary amine-boosted absorption and alcohol-facilitated regeneration - Xiaobin Zhou; Ting Zou; Yunqiong Tang; Shengpeng Mo; Yinming Fan; Bihong Lv; Yanan Zhang; Dunqiu Wang; Yinian Zhu; Zongqiang Zhu; Guohua Jing (Chemical Engineering Journal, 2026)

A probabilistic-based entrainment erosion model combined with the Eulerian-Lagrangian method to simulate snow distribution - Zhenkun Du; Qingwen Zhang; Guolong Zhang; Huamei Mo; Zhongshan Zhang; Feng Fan (Building and Environment, 2026)

DaphTrack: A deep learning-based multidimensional behavior analysis system for neonatal Daphnia magna - Yang Ma; Wenping Xiao; Jinguo Wang; Rongqin Mo; Xiang Kuang; Yuncheng Lv; Xiaoming Fan (Marine Pollution Bulletin, 2026)

Boosting heterogeneous advanced oxidation processes: Curvature-driven nanotube confinement catalysis - Ting Ma; Fan Mo; Haibo Li; Yu Shang; Kaixuan Wang; Xiangqi Nie (Water Research, 2026)

Pt-Cu dual-atom pairs-triggering intermediate activation on single-atom catalysts for enhanced photothermal catalytic VOCs oxidation in cooking oil fumes - Yanan Zhang; Xiaoxue Song; Zichao Chen; Yinming Fan; Xiaobin Zhou; Zongqiang Zhu; Qinglin Xie; Shengpeng Mo; Bing Li; Jianjun Chen; Junhua Li (Journal of Hazardous Materials, 2026)

Development and application of a new simple algorithm for stochastic modeling of daily ground snow loads: A case study in Northeastern China - Huamei Mo; Yuanyuan Li; H.P. Hong; Guolong Zhang; Qingwen Zhang; Feng Fan (Cold Regions Science and Technology, 2026)

Targeting Strategies of Stem Cell-Derived Extracellular Vesicles in the Treatment of Cardiovascular Diseases - Jiaming Fan; Liyun Yao; Jiayi Yao; Shumin Jiang; Lianbo Shao; Yunfang Mo; Ziying Yang; Zhenya Shen (Stem Cell Reviews and Reports, 2026)

Salvianolic Acid B Inhibits Ferroptosis Through ACSL4 Pathway Regulation in sepsis-associated encephalopathy Mice - Xingyao Li; Zhizhun Mo; Yumei Yang; Chunxia Zhao; Shuwen Zhang; Yan Lin; Yuxiang Liu; Ling Wang; Xiaolong Xu; Qingquan Liu; Kai Fan (Molecular Neurobiology, 2026)

An explainable ensemble deep learning model for long-term streamflow forecasting under multiple uncertainties - Xinyuan Qian; Bin Wang; Juan Chen; Yukun Fan; Ran Mo; Chengjing Xu; Weifeng Liu; Jing Liu; Ping-an Zhong (Journal of Hydrology, 2025)

Enhanced water flux and antifouling of a positively charged MoS2/PEI nanofiltration membrane through TA functionalization for effective dye desalination - Guizhen Feng; Kailin Mo; Jun Chen; Huomei Zhang; Zhicheng Cui; Chaoran Fan; Yuntao Zou (Journal of Environmental Chemical Engineering, 2025)

A cross-city transferable convolutional neural network framework for assessing street-scale flood risks in urban networks - Mo Wang; Ji'an Zhuang; Jiayu Zhao; Chuanhao Sun; Jingyao Li; Luqi Zhou; Haowen Fan; Shiqi Zhou; Jinda Qi (Journal of Environmental Management, 2025)

Multivalent copper-carbon-catalyzed persulfate/O2 system: The relation between copper valence and the species of reactive oxygen - Zehui Fan; Zhisen Li; Dan Mo; Jingyang Zhang; Shuyi Yang; Yun Li; Changlong Bi; Chong Peng; Tao E (Journal of Environmental Chemical Engineering, 2025)

Effects of static magnetic fields on the physicochemical and flavor quality of strawberry fruit during cold storage - Fan Liu; Xiaoyue Mo; Sijian Zhou; Jian Wei; Na Yang; Yamei Jin; Xueming Xu (Food Chemistry, 2025)

Automatic immunomagnetic beads clean-up coupled with HPLC-FLD for rapid, simple and high-throughput detection of zearalenone in cereal foods and feeds - Zhiming Xiao; Jun Zhang; Yinji Jin; Bo He; Ting Yao; Jing Tian; Fan Mo; Decheng Suo; Shi Wang; Runxian Li; Lijie Zhang; Shen Hu; et al. (Food Chemistry, 2025)

The dual role of water in CO2 capture by a novel 2-(ethylamino)ethanol-based non-aqueous phase-change absorbent: A net positive effect - Dunqiu Wang; Jingfeng Shen; Dan Wang; Yinming Fan; Shengpeng Mo; Bihong Lv; Yanan Zhang; Yinian Zhu; Zongqiang Zhu; Mi Feng; Xiaobin Zhou; Guohua Jing (Chemical Engineering Journal, 2025)

Structural characterization and oxidative stress modulation activity of an acidic Heteropolysaccharide from Microctis folium - Xiao-lu Liang; Yu-wen Liang; Jing Tian; Fei-fan Mo; Tian-ming Pan; Yan-feng Chen; Xiao-qi Shao; Kun-Ping Li (Carbohydrate Polymers, 2025)

Fluorescent visualization of endoplasmic reticulum stress induced by microplastic pollution via surge of intracellular reactive oxygen species - Le Yang; Xinchao Xia; Fan Li; Qiuhong Mo; Pin Shang; Junbin Li; Yi Li; Yibo Zhou; Zhihe Qing (Analytica Chimica Acta, 2025)

Biodegradable polylactic acid (PLA) copolymer materials: Structural design, synthesis strategy, the relationship between structure and performance, industrial application - Rongrong Ji; Fan Mo; Linwei Liang; Chen Tian; Shixing Dong; Chang Deng; Hao Wu; Ling Zhou; Xipo Zhao (Chemical Engineering Journal, 2025)

Regulating the gel structure and digestive function of myofibrillar protein: The distinct roles of pre-hydrated curdlan and β-glucan - Shuai Jiang; Rongyu Yan; Fan Mo; Qian Liu; Ling Jiang (Food Chemistry, 2025)

CFD investigations into snow loads on tandem-arranged gabled-roofed buildings under mutual interferences - Guolong Zhang; Qingwen Zhang; Huamei Mo; Dong Guo; Xudong Zhi; Jinzhi Wu; Feng Fan (Cold Regions Science and Technology, 2025)

Spatial-temporal heterogeneity of carbon dioxide concentration in Beijing, Tianjin, and Hebei based on interpretable theory - Zihua Liu; Yongqiang Cao; Jiaqi Yao; Fan Mo; Xiaoming Gao; Nan Xu; Haiying Gong; Tong Liu (Atmospheric Research, 2025)

Drought limits microplastic effects on soil greenhouse gas emissions by reducing microbial diversity - Jianling Wang; Huanhuan Liu; Aurang Zeb; Qi Wang; Fan Mo; Ruiying Shi; Yuexing Zhao; Chuan Yin; Zhengguo Song; Weitao Liu (Journal of Environmental Management, 2025)

Catalytic fast pyrolysis of waste battery separators with limited removal of the Al2O3 layer for selective aromatic hydrocarbons production over HZSM-5 catalyst - Li Zhao; Wan-zhao Huang; Shi-guan Yang; Qi Niu; Shi-yu Feng; Pu-cheng Wang; Ying Mo; Yu-han Fan; Kai Li; Qiang Lu (Journal of Environmental Management, 2025)

Decoding the genetic links between substance use disorder and cancer vulnerability - Xin Su; Xiaoyan Mo; Jun Kan; Fan Yang; Bei Zhang; Yuanyuan Huang (Psychopharmacology, 2025)

Automated detection and recognition of oocyte toxicity by fusion of latent and observable features - Shuai Huang; Kun Zhao; Chu Chu; Qi Fan; Yuanyuan Fan; Yongqi Luo; Yiming Li; Ke Mo; Guanghui Dong; Huiying Liang; Xiaomiao Zhao (Journal of Hazardous Materials, 2025)

Adjusting Co ratios to control the unsaturated Mn defects in nanostick-assembled CoOx@MnOx double layered sphere catalysts for highly active photothermocatalysis of acetone/ethyl acetate and NO without ammonia - Yinming Fan; Weihan Wu; Yanping Zhang; Yinian Zhu; Shengpeng Mo; Lei Liao; Mingming Fu; Yanan Zhang; Xiaobin Zhou; Zongqiang Zhu (Journal of Environmental Chemical Engineering, 2025)

Thermal management of photovoltaic systems using cascade phase change material module - Tingting Wu; Lianjian Mo; Guiyang Ye; Yanxin Hu; Changxiang Fan; Mingjiang Zeng; Shuting Cai; Mengjie Song (Building and Environment, 2025)

Assessing the impact of land use changes on urban heat risk under different development scenarios: A case study of Guangzhou in China - Binwei Zou; Chengliang Fan; Jianjun Li; Mo Wang; Yundan Liao; Xiaoqing Zhou (Sustainable Cities and Society, 2025)

Illuminating the nexus between non-biodegradable microplastics and soil nitrogen dynamics: A modulation through plant-derived organic matter - Zelin Hou; Fan Mo; Qixing Zhou; Dawen Gao; Tong Zheng; Zongxin Tao; Yin Lu (Journal of Hazardous Materials, 2025)

Microbiome-metabolome correlations across vertical stratification in Jiupei of strong-flavored baijiu fermentation - Haiyan Xu; Qinglan Tang; Kequan Fan; Menghua Liu; Lingxu Wang; Kai Mo; Zhancheng Xu; Wenxue Zhang (Food Research International, 2025)

Deep blue OLEDs satisfying BT. 2020 standard enabled by a simple-structured multiple resonance emitter with CIEy coordinate of 0.02 - Hao Wu; Yi-Zhong Shi; Mo-Yuan Li; Xiao-Chun Fan; Hui Wang; Tong-Yuan Zhang; Jia-Xiong Chen; Jia Yu; Kai Wang (Chemical Engineering Journal, 2025)

Modeling and mechanistic understanding of vertical dissolved methane transport in integrated vertical flow constructed wetlands (IVCWs) - Ru Xue; Ke Zhang; Xiaoling Liu; Bing Jiang; Hongbing Luo; Mei Li; You Mo; Cheng Liu; Lin Li; Wei Chen; Lin Cheng; Jia Chen; et al. (Journal of Water Process Engineering, 2025)

Construction of Fe-Mn-La/Ce@biochar electrodes 3D/HEF systems for efficient electro-Fenton degradation of coking wastewater: performance and mechanism insights - Wenjie Ren; Qiaoyun Zhu; Chaofan Mo; Xinyu Ma; Wanqiang Zhang; Huanhuan Tang; Zili Fan; Yi Wang; Guozhi Fan; Lei Zhang (Journal of Environmental Management, 2025)

Regulated synthesis of 3D Mn2O3 hollow microspheres derived from Mn-BTC for concentrating solar-driven photothermal ethyl acetate oxidation - Zichao Chen; Jiaxi Zheng; Shengmei Huang; Lili Huang; Yinming Fan; Xiaobin Zhou; Yanan Zhang; Zongqiang Zhu; Qinglin Xie; Shengpeng Mo; Daiqi Ye (Journal of Environmental Chemical Engineering, 2025)

Development of a high-performance natural edible film from chitosan, dialdehyde cellulose, and proanthocyanidin with enhanced antioxidant activity - Ruijing Jia; Lianghuan Huang; Meiyi Zou; Qiong Jiang; Ningjing Sun; Kehao Fan; Jialong Wen; Liuting Mo; Wei Gao; Zhiyong Qin (Food Hydrocolloids, 2025)

Highly tough and responsible ionic liquid/polyvinyl alcohol-based hydrogels for stretchable electronics - Pengcheng Zhou; Fan Mo; Zichong Ji; Jiawei Yang; Hongzhong Du; Zonglei Wang; Hossam Haick; Yan Wang (Science Bulletin, 2025)

Screening characteristic VOC species, health hazards, and odor pollutants in the grain and oilseed milling industry of China - Xia Yang; Ying Liu; Jiale Fan; Gexiang Chen; Ziwei Mo; Xiongbo Chen (Environmental Pollution, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

Research on controlling measures of snowdrifts around Arctic ground-based buildings through shape optimization - Qingwen Zhang; Guolong Zhang; Ruixiang Zheng; Huamei Mo; Xudong Zhi; Jinzhi Wu; Feng Fan (Cold Regions Science and Technology, 2025)

How do urban-rural and regional summer heat exposures evolve? A case study of 301 cities in China from 2000 to 2020 - Binwei Zou; Chengliang Fan; Mo Wang; Jianjun Li; Xiaoqing Zhou; Yundan Liao (Building and Environment, 2025)

circTP63-N suppresses the proliferation and metastasis of nasopharyngeal carcinoma via engaging with HSP90AB1 to modulate the YAP1/Hippo signaling pathway - Dan Wang; Sicheng Zuo; Junshang Ge; Hongke Qu; Jie Wu; Na Yi; Lei Shi; Yumin Wang; Yongzhen Mo; Chunmei Fan; Yi He; Pan Chen; et al. (Science China Life Sciences, 2025)

Supplementation with L-kynurenine during in vitro maturation improves bovine oocytes developmental competence through its antioxidative action - Canqiang Lu; Yun Feng; Zhenhua Tang; Ruru Jia; Fan Xia; Tingzi Yu; Heng Wang; Hongfang Mo; Deshun Shi; Fenghua Lu (Theriogenology, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

A fully integrated, non-invasive, and multimodal wearable device for sweat stimulation, collection and multiple physiological signals analysis - Yuetao Zhang; Zijie Li; Xuejiao Fan; Yan Liu; Zhiqi Li; Ziwei Zheng; Zixin Lin; Wenshan Zhang; Qingci Mu; Guangquan Mo; Yong Xia; Lei Mou (Chemical Engineering Journal, 2025)

Novel asymmetrical double-layer structural adhesive hydrogels with synergetic neuroprotection and angiogenesis effect for diabetic wound healing - Zhihong Su; Wanjun Zhang; Zizeng Mo; Peihua Zhang; Zeyong Wu; Haili Huang; Xianmou Fan (Chemical Engineering Journal, 2025)

Two-way role of boron in microalgal-bacterial granular sludge: Enhanced signal communication for efficient metabolism - Renhui Wan; Fan Mo; Leyan Chen; Junguo He; Senlin Shao; Huizhi Hu (Bioresource Technology, 2025)

Construction of multi-pathway electron transfer channel: Mechanism on non-radical to radical promotion in electrocatalysis - Jingyang Zhang; Zhisen Li; Zehui Fan; Dan Mo; Shuyi Yang; Yun Li; E Tao (Chemical Engineering Journal, 2025)

QSAR models for predicting key hormesis parameters of quinolone antibiotic mixtures on Vibrio qinghaiensis sp.-Q67 - Ling-Yun Mo; Si-Tong Long; Xia-Chang-Li Xu; Li-Tang Qin; Fan Jiang (Science of The Total Environment, 2024)

Response of Ceratophyllum demersum L. and its epiphytic biofilms to 6PPD and 6PPD-Q exposure: Based on metabolomics and microbial community analysis - Xiang Li; Weitao Liu; Yichen Ge; Ruiying Shi; Chuan Yin; Jinzheng Liu; Yuexing Zhao; Qi Wang; Jianling Wang; Fan Mo; Aurang Zeb; Miao Yu (Journal of Hazardous Materials, 2024)

Rhizosphere Ecological Characteristics of Trifolium repens L. under Cadmium Stress: with Focus on the Spatial Distribution Pattern of Enzyme Activity - Chenxi Zhang; Haibo Li; Fan Mo; Mingshuai Wang; Yaran Bai; Haotian Ma; Bingqian Gao; Rui Wang (Journal of Soil Science and Plant Nutrition, 2024)

Decoding the genetic landscape of juvenile dermatomyositis: insights from phosphorylation-associated single nucleotide polymorphisms - Huan Zhang; Zhentao Zhang; Kedi Fan; Hongru Chen; Yufan Guo; Xingbo Mo (Immunogenetics, 2024)

Symbiotrophs dominate rhizosphere soil fungal community stability of the Cathaya argyrophylla - Zhibo Zhou; Peng Xie; Kerui Huang; Ping Mo; Aihua Deng; Shaogang Fan; Binbin Long; Yun Wang (Applied Soil Ecology, 2024)

Evaluation and comparison of iohexol elimination by UV/peroxymonosulfate and UV/persulfate processes: Radical roles, influence factors and iodinated trihalomethanes formation - Chen-Cheng Mo; Fu-Xiang Tian; Bin Xu; Fan Lai; Yu-Qiong Gao; Yan Ma; Zi-Han Feng; Zi-Jian Yao; Dong-Su Bi; Xiao-Jun Hu (Journal of Water Process Engineering, 2024)

Urban flooding damage prediction in matrix scenarios of extreme rainfall using a convolutional neural network - Mo Wang; Haowen Fan; Haojun Yuan; Dongqing Zhang; Jin Su; Shiqi Zhou; Qifei Zhang; Jianjun Li (Journal of Hydrology, 2024)

Insights into the in vitro digestibility and rheology properties of myofibrillar protein with different incorporation types of curdlan - Shuai Jiang; Fan Mo; Qian Liu; Ling Jiang (Food Chemistry, 2024)

The potential of glycinin basic peptide derived from soybean as a promising candidate for the natural food additive and preservative: A review - Hou-Qi Ning; Hai-Run Fan; Chun-Ling Yang; Gui-Jin Sun; Ying-Qiu Li; Hai-Zhen Mo (Food Chemistry, 2024)

Automated counting and classifying Daphnia magna using machine vision - Yang Ma; Wenping Xiao; Jinguo Wang; Xiang Kuang; Rongqin Mo; Yanfang He; Jianfeng Feng; Hengling Wei; Liwen Zheng; Yufei Li; Peixin Liu; Hao He; et al. (Aquatic Toxicology, 2024)

Power management and optimization of marine hybrid propulsion systems: A combinator surface methodology - Fan Gao; Astrid H. Brodtkorb; Mehdi Zadeh; Sigrid Marie Mo (Ocean Engineering, 2024)

Feasibility study of denitrification catalyst prepared from badam shell biochar - Bo Song; Xinyu Mo; Zhenxing Shen; Qin Peng; Hao Fan; Jian Sun; Liu Yang (Journal of Environmental Chemical Engineering, 2024)

Effects of Aeromonas infection on the immune system, physical barriers and microflora structure in the intestine of juvenile grass carp (Ctenopharyngodon idella) - Meixing Guo; Ran Peng; Kelan Jin; Xia Zhang; Huilan Mo; Xiang Li; Fufa Qu; Jianzhou Tang; Shenping Cao; Yonghua Zhou; Zhimin He; Zhuangwen Mao; et al. (Fish & Shellfish Immunology, 2024)

Multimodal enhancement of ferroptosis for synergistic cascade colorectal cancer therapy - Ziying Wu; Kun Chen; Weisheng Mo; Yue Wang; Xiewei Lin; Zhien Lan; Caijing Mo; Haocheng Wang; Xiaoying Li; Xingdi Fan; Hungchen Chen; Zhilin Shu; et al. (Chemical Engineering Journal, 2024)

The pivotal role of phosphorus level gradient in regulating nitrogen cycle in wetland ecosystems - Fan Mo; Chenghao Li; Qixing Zhou (Science of The Total Environment, 2024)

Cu-optimized long-range interaction between Co nanoparticles and Co single atoms: Improved Fenton-like reaction activity - Fan Mo; Zelin Hou; Qixing Zhou; Xixi Chen; Weitao Liu; Wendan Xue; Qi Wang; Jianling Wang; Tong Zheng; Zongxin Tao (Science Bulletin, 2024)

Investigation on the static performance of geogrid reinforced aeolian sand railway embankment: Field test and discrete element simulation - Wei Du; Rusong Nie; Yanlu Qi; Bo Ruan; Fan Mo (Geotextiles and Geomembranes, 2024)

Fish decay-accelerating factor (DAF) regulates intestinal complement pathway and immune response to bacterial challenge - Xia Zhang; Yuhan Zhang; Ting Wu; Hao He; Ran Peng; Kelan Jin; Huilan Mo; Fufa Qu; Jianzhou Tang; Yonghua Zhou; Yalin Yang; Zhigang Zhou; et al. (Fish & Shellfish Immunology, 2024)

Highly sensitive formaldehyde gas sensor based on SnO2/Zn2SnO4 hybrid structures - Guijun Fan; Jian Guan; Hang Yu; Qiuyi Zhu; Ning Han; Jinhan Mo; Yunfa Chen (Building and Environment, 2024)

The origins of odor (β-cyclocitral) under different water nutrient conditions: Algae or submerged plants? - Yu Lin; Chaoyue Cheng; Yutai Dai; Weijie Li; Jiping Chen; Mo Chen; Ping Xie; Qiang Gao; Xiaoyue Fan; Xuwei Deng (Science of The Total Environment, 2024)

Analysing the influence of surface greening on soil conservation in China using satellite remote sensing - Jiaqi Yao; Jing Li; Yongqiang Cao; Min Chen; Chenyue Zhang; Fan Mo; Guodong Jia; Huanyu Chang; Jianjun Wu (Journal of Hydrology, 2024)

Co-ZIF-derived dual Co and Co3S4 nanoparticles encapsulated in N-doped carbon matrix for efficient photocatalytic CO2 reduction - Lili Huang; Shengpeng Mo; Xin Zhao; Jiangjing Zhou; Yanan Zhang; Xiaobin Zhou; Yinming Fan; Qinglin Xie; Daiqi Ye (Journal of Environmental Chemical Engineering, 2024)

High-throughput analysis of hazards in novel food based on the density functional theory and multimodal deep learning - Lin Shi; Wei Jia; Rong Zhang; Zibian Fan; Wenwen Bian; Haizhen Mo (Food Chemistry, 2024)

Investigation of the Antiviral Mechanism of Curcumin Analog EF-24 against Siniperca cachuatsi Rhabdovirus - Pei-Mo Ju; Shi-Wei Ma; Yi-Yang Li; Shi-Fan Zhang; Jun Li; Guang-Zhou Zhou (Fishes, 2024)
Siniperca chuatsi rhabdovirus (SCRV) is a major strain of viral fish virus resulting in multiple transmissions and devastating damage in aquaculture. Currently, there are no available approved therapeutics. In this study, we screened and identified a novel curcumin analog (EF-24) for evaluating its in vitro anti-SCRV properties and potential molecular mechanisms. Present results demonstrated that EF-24 could strongly delay the occurrence of cytopathic effects (CPEs) in epithelioma papulosum cyprinid cells (EPCs) and inhibit SCRV replication and viral nucleoprotein expression in the early stages of infection by the time-of-addition assay. Furthermore, flow cytometry analysis after Annexin V-FITC/PI double staining and immunofluorescence microscopy observation after JC-1 incubation showed that EF-24 downregulated cell mitochondrial apoptosis induced by SCRV. The enzymatic activities of caspase-3 and caspase-9 were also reduced after EF-24 treatment, indicating that EF-24 may protect cells from SCRV infection by decreasing mitochondrial intrinsic apoptosis in infected cells. Collectively, we demonstrated for the first time that the curcumin analog EF-24 possesses antiviral ability against SCRV, suggesting its potential for effective control of fish rhabdovirus spreading.

Study on the performance and mechanism of cobaltous ion removal from water by a high-efficiency strontium-doped hydroxyapatite adsorbent - Zongqiang Zhu; Shuangshuang Liu; Yinian Zhu; Hao He; Jun Zhang; Xiaoxin Mo; Shen Tang; Yinming Fan; Lihao Zhang; Xiaobin Zhou (Environmental Science and Pollution Research, 2024)

Occurrence, distribution, and risk assessment of antibiotics in a typical aquaculture area around the Dongzhai Harbor mangrove forest on Hainan Island - Tuan-Tuan Wang; Shuai Shao; Shi-Di Fan; Wang-Qing Tang; Jiang-Wei Miao; Sai Wang; Xiao-Cong Cao; Chuan Liu; Guang-Guo Ying; Zhong-Bing Chen; Hai-Long Zhou; Xiao-Ping Diao; et al. (Science of The Total Environment, 2024)

N, S, and Cl tri-doped carbon boost the switching of radical to non-radical pathway in Fenton-like reactions: Synergism of N species and defects - Shizhe Xu; Pengfei Wang; Xueyue Mi; Yueping Bao; He Zhang; Fan Mo; Qixing Zhou; Sihui Zhan (Journal of Hazardous Materials, 2024)

China's National Reserve Forest Project contribution to carbon neutrality and path to profitability - Fan Zhang; Mo Li; Shouhong Zhang; Jiakai Liu; Yufei Ren; Yini Cao; Feilong Li (Forest Policy and Economics, 2024)

Partitioning mechanisms and film formations of DEHP on realistic indoor airborne particles and road dust - Zhuo Chen; Fanxuan Xia; Yujie Fan; Yi Jiang; Ying Xu; Jinhan Mo (Building and Environment, 2024)

Hierarchically ordered microporous Ag2S QDs-CoOx/NC nanostructures for enhancing photocatalytic CO2 reduction to chemical fuels - Shengpeng Mo; Lili Huang; Xin Zhao; Jun Li; Xuegang Ding; Xiaobin Zhou; Yanan Zhang; Yinming Fan; Mingming Fu; Hongxiang Zhu; Qinglin Xie; Daiqi Ye (Fuel, 2024)

Molecular and geochemical characteristics of lignite in different plant sources evaluated using unsupervised analyses - Yang-Yang Xu; Xing Fan; Feng-Yun Ma; Wen-Long Mo; Xiang Bai; Xian-Yong Wei; Peter N Kuznetsov (Fuel, 2024)

Inhibiting effect of 2-amino-2-methyl-1-propanol on gelatinous product formation in non-aqueous CO2 absorbents: Experimental study and molecular understanding - Chao Liu; Guohua Jing; Zongqiang Zhu; Yinming Fan; Shengpeng Mo; Yanan Zhang; Dunqiu Wang; Bihong Lv; Mingming Fu; Xiaobin Zhou (Chemical Engineering Journal, 2024)

Long‐term nitrogen and phosphorus addition have stronger negative effects on microbial residual carbon in subsoils than topsoils in subtropical forests - Linjie Fan; Yuewei Xue; Donghai Wu; Meichen Xu; Andi Li; Baixin Zhang; Jiangming Mo; Mianhai Zheng (Global Change Biology, 2024)
Highly weathered lowland (sub)tropical forests are widely recognized as nitrogen (N)‐rich and phosphorus (P)‐poor, and the input of N and P affects soil carbon (C) cycling and storage in these ecosystems. Microbial residual C (MRC) plays a crucial role in regulating soil organic C (SOC) stability in forest soils. However, the effects of long‐term N and P addition on soil MRC across different soil layers remain unclear. This study conducted a 12‐year N and P addition experiment in two typical subtropical plantation forests dominated by Acacia auriculiformis and Eucalyptus urophylla trees, respectively. We measured plant C input (fine root biomass, fine root C, and litter C), microbial community structure, enzyme activity (C/N/P‐cycling enzymes), mineral properties, and MRC. Our results showed that continuous P addition reduced MRC in the subsoil (20–40 cm) of both plantations ( A. auriculiformis : 28.44% and E. urophylla : 28.29%), whereas no significant changes occurred in the topsoil (0–20 cm). N addition decreased MRC in the subsoil of E. urophylla (25.44%), but had no significant effects on A. auriculiformis . Combined N and P addition reduced MRC (34.63%) in the subsoil of A. auriculiformis but not in that of E. urophylla . The factors regulating MRC varied across soil layers. In the topsoil (0–10 cm), plant C input (the relative contributions to the total variance was 20%, hereafter) and mineral protection (47.2%) were dominant factors. In the soil layer of 10–20 cm, both microbial characteristics (41.3%) and mineral protection (32.3%) had substantial effects, whereas the deeper layer (20–40 cm) was predominantly regulated by microbial characteristics (37.9%) and mineral protection (18.8%). Understanding differential drivers of MRC across soil depth, particularly in deeper soil layers, is crucial for accurately predicting the stability and storage of SOC and its responses to chronic N enrichment and/or increased P limitation in (sub)tropical forests.

Assessing stress responses in potherb mustard (Brassica juncea var. multiceps) exposed to a synergy of microplastics and cadmium: Insights from physiology, oxidative damage, and metabolomics - Jianling Wang; Weitao Liu; Xue Wang; Aurang Zeb; Qi Wang; Fan Mo; Ruiying Shi; Jinzheng Liu; Miao Yu; Jiantao Li; Zeqi Zheng; Yuhang Lian (Science of The Total Environment, 2024)

Ecosystem health evaluation of urban rivers based on multitrophic aquatic organisms - Zhen Cui; Wenting Fan; Cheng Chen; Kangle Mo; Qiuwen Chen; Qiang Zhang; Rong He (Journal of Environmental Management, 2024)

Conformational isomerization imparts low concentration dependence to multiple resonance thermally activated delayed fluorescence (MR-TADF) emitters - Hao Wu; Yi-Zhong Shi; Mo-Yuan Li; Xiao-Chun Fan; Feng Huang; Kai Wang; Jia Yu; Xiao-Hong Zhang (Chemical Engineering Journal, 2024)

Does spatiotemporal heterogeneity matter? Air transport and the rise of high-tech industry in China - Fan Xiao; Jiaoe Wang; Meicheng Xiong; Huihui Mo (Applied Geography, 2024)

Performance and mechanism analysis of sludge-based biochar loaded with Co and Mn as photothermal catalysts for simultaneous removal of acetone and NO at low temperature - Hongqiang Wang; Sheng Huang; Lei Liao; Shengpeng Mo; Xiaobin Zhou; Yinming Fan (Environmental Science and Pollution Research, 2023)

Crop NDVI time series construction by fusing Sentinel-1, Sentinel-2, and environmental data with an ensemble-based framework - Dairong Chen; Haoxuan Hu; Chunhua Liao; Junyan Ye; Wenhao Bao; Jinglin Mo; Yue Wu; Taifeng Dong; Hong Fan; Jie Pei (Computers and Electronics in Agriculture, 2023)

Adulteration of endogenous substances as a next challenge in dairy safety: High-throughput analysis of flavours in goat milk based on the molecular mechanism of flavouring components dynamic changes - Lin Shi; Wei Jia; Rong Zhang; Zibian Fan; Haizhen Mo (Trends in Food Science & Technology, 2023)

Advances in investigating microcystin-induced liver toxicity and underlying mechanisms - Tong Li; Xinting Fan; Meihan Cai; Yuanyuan Jiang; Yaqi Wang; Peishuang He; Juan Ni; Aili Mo; Cuiying Peng; Jun Liu (Science of The Total Environment, 2023)

The interfacial interaction between Dechlorane Plus (DP) and polystyrene nanoplastics (PSNPs): An overlooked influence factor for the algal toxicity of PSNPs - Qi Wang; Weitao Liu; Lingzuo Meng; Aurang Zeb; Fan Mo; Jianling Wang; Ruiying Shi (Science of The Total Environment, 2023)

Recycling of the waste battery: Effect of waste battery on property of asphalt and environmental impact evaluation - Yongjun Meng; Jun Lai; Liupeng Fan; Shuyi Mo; Chaoliang Gou; Chunyu Zhang (Science of The Total Environment, 2023)

Strontium alleviated the growth inhibition and toxicity caused by cadmium in rice seedlings - Jun Liu; Xinting Fan; Yuanyuan Jiang; Juan Ni; Aili Mo; Meihan Cai; Tong Li; Yaqi Wang; Peishuang He; Shiyu Hu; Tangjian Peng; Cuiying Peng; et al. (Science of The Total Environment, 2023)

N-doped porous carbon material derived by MOFs calcined in proper oxygen atmosphere as high-performance catalyst for the low-temperature NH3-SCR - Jiexuan Zhu; Donghai Mo; Lin Tao; Jinfeng Li; Shiying Fu; Lihui Dong; Bin Li; Zhengjun Chen; Minguang Fan (Journal of Environmental Chemical Engineering, 2023)

In-situ construction of Li-Ag/LiF composite layer for long cycled all-solid-state Li metal battery - Qianxiao Fan; Wendi Zhang; Yilong Jin; Dongmei Zhang; Xianglong Meng; Wanxiong Peng; Jinhui Wang; Jinshan Mo; Kai Liu; Lehao Liu; Meicheng Li (Chemical Engineering Journal, 2023)

Novel amino-modified bamboo-derived biochar-supported nano-zero-valent iron (AMBBC-nZVI) composite for efficient Cr(VI) removal from aqueous solution - Xiaobin Zhou; Yingxue Wang; Huili Liu; Yanan Zhang; Yinming Fan; Shengpeng Mo; Huaxia Li; Junyi Wang; Hua Lin (Environmental Science and Pollution Research, 2023)

Cadmium affects the growth, antioxidant capacity, chlorophyll content, and homeostasis of essential elements in soybean plants - Jun Liu; Juan Ni; Aili Mo; Xinting Fan; Yuanyuan Jiang; Hongyan Xie; Jingsong Hu; Yunhua Zhu; Cuiying Peng; Fei Yang (South African Journal of Botany, 2023)

Elucidating response mechanisms at the metabolic scale of Eisenia fetida in typical oil pollution sites: A native driver in influencing carbon flow - Zelin Hou; Fan Mo; Qixing Zhou (Environmental Pollution, 2023)

Overview and countermeasures of cancer burden in China - Yian Wang; Qijia Yan; Chunmei Fan; Yongzhen Mo; Yumin Wang; Xiayu Li; Qianjin Liao; Can Guo; Guiyuan Li; Zhaoyang Zeng; Wei Xiong; He Huang (Science China Life Sciences, 2023)

Iron oxide nanoparticles in the soil environment: Adsorption, transformation, and environmental risk - Zongxin Tao; Qixing Zhou; Tong Zheng; Fan Mo; Shaohu Ouyang (Journal of Hazardous Materials, 2023)

A new model to accurately measure the radon exhalation rate from soil using AlphaGUARD - Shuaibin Liu; Tao Hu; Fen Lin; Zhongkai Fan; Ruomei Xie; Shuai Yuan; Jiulin Wu; Haibo Yi; Yixiang Mo; Jiale Sun; Linquan Chen; Huiying Li; et al. (Journal of Environmental Radioactivity, 2023)

Application of super-cooled storage of aquatic products: A review - Xin-Yu Liu; Xue-Lai Zhang; Guan-Bang Wang; Fan-Yang Mo; Xin-Rong Zhang (International Journal of Refrigeration, 2023)

Potential contribution of chlorella vulgaris to carbon–nitrogen turnover in freshwater ecosystems after a great sandstorm event - Zelin Hou; Qixing Zhou; Yingying Xie; Fan Mo; Weilu Kang; Qi Wang (Environmental Research, 2023)

Designing multi-layered MOF-on-MOF-transformed core double-shell FeSx@ZnS@CoSx heterojunction for enhanced CO2 photoreduction with water vapor - Lili Huang; Shengpeng Mo; Xin Zhao; Jiangjing Zhou; Xiaobin Zhou; Yanan Zhang; Mingming Fu; Yinming Fan; Qinglin Xie; Daiqi Ye; Yunfa Chen (Chemical Engineering Journal, 2023)

Efficient active contours with optical physical parameters for shoreline extraction: a general method and novel framework - Bo Ai; Xiao Zhang; Yaru Zhang; Zhen Wen; Fan Mo; Jiaqi Yao (International Journal of Remote Sensing, 2023)

Selenium Reduces Rice Plant Tissues Cadmium and Increases the Yield, Quality, and Edible Safety of Rice Grain, and May Affect the Taste of Cooked Rice - Jun Liu; Aili Mo; Juan Ni; Xinting Fan; Yuanyuan Jiang (Journal of Soil Science and Plant Nutrition, 2023)

Flotation separation of coal dust from foundry dust enhanced by pre-soaking assisted mechanical stirring - Xiaolong Gong; Shengli Hu; Xinwang Liu; Mo Yang; Wenming Jiang; Zitian Fan (Journal of Environmental Management, 2023)

Variations of methane fluxes and methane microbial community composition with soil depth in the riparian buffer zone of a sponge city park - Ru Xue; Ke Zhang; Xiaoling Liu; Bing Jiang; Hongbing Luo; Mei Li; You Mo; Cheng Liu; Lin Li; Liangqian Fan; Wei Chen; Lin Cheng; et al. (Journal of Environmental Management, 2023)

Rice irrigation water efficiency improvement: An AquaCrop-based optimization modeling approach - Peixi Tang; Nan Li; Mo Li; Fan Zhang; Qiang Fu; Yaowen Xu; Dong Liu (European Journal of Agronomy, 2023)

Integrated physio-biochemical and transcriptomic analysis revealed mechanism underlying of Si-mediated alleviation to cadmium toxicity in wheat - Haitao Liu; Qiujuan Jiao; Lina Fan; Ying Jiang; Mohammed Nasser Alyemeni; Parvaiz Ahmad; Yinglong Chen; Mo Zhu; Haiping Liu; Ying Zhao; Fang Liu; Shiliang Liu; et al. (Journal of Hazardous Materials, 2023)

PARP molecular functions and applications of PARP inhibitors in cancer treatment - Yuhan Guo; Boyang Fan; Mo Li (Genome Instability & Disease, 2023)

Evaluation of in vitro toxicity information for zebrafish as a promising alternative for chemical hazard and risk assessment - Jing Yang; Yolina Yu Lin Wang; Syed Shabi Ul Hassan Kazmi; Jiezhang Mo; Hailin Fan; Yuwen Wang; Wenhua Liu; Zhen Wang (Science of The Total Environment, 2023)

Transcatheter closure of perimembranous ventricular septal defect using a novel fully bioabsorbable occluder: multicenter randomized controlled trial - Shouzheng Wang; Zefu Li; Yunbing Wang; Tianli Zhao; Xuming Mo; Taibing Fan; Jianhua Li; Tao You; Rundi Deng; Wenbin Ouyang; Weiwei Wang; Chuangnian Zhang; et al. (Science Bulletin, 2023)

Triclosan toxicity in a model cyanobacterium (Anabaena flos-aquae): Growth, photosynthesis and transcriptomic response - Jiezhang Mo; Linrong Han; Runnan Lv; Michael W.L. Chiang; Rong Fan; Jiahua Guo (Journal of Environmental Sciences, 2023)

Hollow cavity engineering of MOFs-derived hierarchical MnOx structure for highly efficient photothermal degradation of ethyl acetate under light irradiation - Jun Li; Shengpeng Mo; Xuegang Ding; Lili Huang; Xiaobin Zhou; Yinming Fan; Yanan Zhang; Mingming Fu; Qinglin Xie; Daiqi Ye (Chemical Engineering Journal, 2023)

Enhanced carbon emission driven by the interaction between functional microbial community and hydrocarbons: An enlightenment for carbon cycle - Zelin Hou; Qixing Zhou; Fan Mo; Weilu Kang; Shaohu Ouyang (Science of The Total Environment, 2023)

An inorganic-organic-polymeric nanovehicle for targeting delivery of doxorubicin: Rational assembly, pH-stimulus release, and dual hyperthermia/chemotherapy of hepatocellular carcinoma - Jianying Yang; Zhao Wang; Chunhong Mo; Haikun Luo; Shuting Li; Qian Mo; You Qin; Fan Yang; Xinchun Li (Journal of Photochemistry and Photobiology B: Biology, 2023)

Characteristics and environmental and health impacts of volatile organic compounds in furniture manufacturing with different coating types in the Pearl River Delta - Yang Liu; Chunling Zeng; Meiyuan Wang; Xia Shao; Yijuan Yao; Guangqi Wang; Yinsong Li; Mo Hou; Liya Fan; Daiqi Ye (Journal of Cleaner Production, 2023)

Association between maternal exposure to per- and polyfluoroalkyl substances and serum markers of liver function during pregnancy in China: A mixture-based approach - Qian Liao; Peng Tang; Haoran Fan; Yanye Song; Jun Liang; Huishen Huang; Dongxiang Pan; Meile Mo; LeiLei; Mengrui Lin; Jiehua Chen; Huanni Wei; et al. (Environmental Pollution, 2023)

The evaluation of N/P fate using the SPARROW model: a case study in an arid and semi-arid region, northern China - Haitao Chen; Jincheng Yin; Menglai Song; Han Ding; Fan Mo; Qiuru Ren; Guoguang Li; Shuang Song; Yuqiu Wang (Environmental Science and Pollution Research, 2023)

Efficient photocatalytic degradation of high-concentration moxifloxacin over dodecyl benzene sulfonate modified graphitic carbon nitride: Enhanced photogenerated charge separation and pollutant enrichment - Pengfei Sun; Yi Liu; Fan Mo; Meixuan Wu; Yingping Xiao; Xingning Xiao; Wen Wang; Xiaoping Dong (Journal of Cleaner Production, 2023)

Weavable, large-scaled, rapid response, long-term stable electrochemical fabric sensor integrated into clothing for monitoring potassium ions in sweat - Lili Mo; Xiangda Ma; Longfei Fan; John H. Xin; Hui Yu (Chemical Engineering Journal, 2023)

A 2D mesoporous hydrazone covalent organic framework for selective detection and ultrafast recovery of Au(III) from electronic waste - Li Zhang; Jia-Qi Fan; Qiong-Qing Zheng; Sai-Jin Xiao; Cheng-Rong Zhang; Shun-Mo Yi; Xin Liu; Wei Jiang; Quan-Gen Tan; Ru-Ping Liang; Jian-Ding Qiu (Chemical Engineering Journal, 2023)

Toxic effects of glyphosate on histopathology and intestinal microflora of juvenile Litopenaeus vannamei - Binhua Mo; Jingping Li; Guowei Liao; Lei Wang; Lanfen Fan (Aquatic Toxicology, 2023)

Effect of solvent swelling with different enhancement methods on the microstructure and pyrolysis performance of Hefeng subbituminous coal - Hui Kan; Yue Wang; Wen-Long Mo; Xian-Yong Wei; Hong-Yu Mi; Kong-Jun Ma; Mei-Xia Zhu; Wen-Cang Guo; Jia Guo; Jun-Min Niu; Xing Fan (Fuel, 2023)

Effect of sequential thermal dissolution on the structure and pyrolysis characteristics of Naomaohu lignite - Xiao-Bo Hu; Hao Xu; Wen-Long Mo; Xing Fan; Wen-Cang Guo; Jia Guo; Jun-Min Niu; Hong-Yu Mi; Ya-Ya Ma; Xian-Yong Wei (Fuel, 2023)

Porous Cobalt-nickel phosphides prepared from Al-doped NiCo-LDH precursors for supercapacitor and electrocatalysis applications - Ruonan Liu; Lulu Chen; Fei Mo; Haiyan Song; Guang Yang; Chunxia Chen; Xiaoliang Wu; Yichao Huang; Zhuangjun Fan (Chemical Engineering Journal, 2023)

Development of a matrix-based candidate reference material for human glycated albumin using isotope-dilution liquid chromatography/tandem mass spectrometry - Rui Zhang; Rui Zhao; Wenhua Ren; Mo Wang; Gaowei Fan; Jie Shi; Yichuan Song; Xiaojie Zhou; Qingtao Wang (Analytica Chimica Acta, 2023)

An Updated Review on Ag NP Effects at Organismal Level: Internalization, Responses, and Influencing Factors - Fan Mo; Haibo Li; Yuqing He; Qixing Zhou (Reviews of Environmental Contamination and Toxicology, 2022)

Circular RNA circCCNB1 inhibits the migration and invasion of nasopharyngeal carcinoma through binding and stabilizing TJP1 mRNA - Mengyao Zhao; Yian Wang; Fenghua Tan; Lingyun Liu; Xiangchan Hou; Chunmei Fan; Le Tang; Yongzhen Mo; Yumin Wang; Qijia Yan; Zhaojian Gong; Zheng Li; et al. (Science China Life Sciences, 2022)

Ectopic Expression of Erigeron breviscapus JAZ1 Affects JA-Induced Development Processes in Transgenic Arabidopsis - Mo Chen; Wei Zhang; Mi Yan; Simei He; Yingchun Lu; Guanghui Zhang; Bing Hao; Wei Fan; Yanru Hu; Shengchao Yang (Plant Molecular Biology Reporter, 2022)

Comprehensive analysis of TCR repertoire of COVID-19 patients in different infected stage - Guangyu Wang; Yongsi Wang; Shaofeng Jiang; Wentao Fan; Chune Mo; Weiwei Gong; Hui Chen; Dan He; Jinqing Huang; Minglin Ou; Xianliang Hou (Genes & Genomics, 2022)

Cavin-1 promotes M2 macrophages/microglia polarization via SOCS3 - Wei Huang; Yiyi Hong; Wenjing He; Li Jiang; Wen Deng; Biyan Peng; Fen Tang; Chaolan Shen; Qianqian Lan; Hui Huang; Haibin Zhong; Jian Lv; et al. (Inflammation Research, 2022)

Physiological homeostasis alteration and cellular structure damage of Chlorella vulgaris exposed to silver nanoparticles with various microstructural morphologies - Ningcan Deng; Haibo Li; Yinghua Li; Fan Mo; Mingshuai Wang; Zhe Li; Xi Chen; Jianing Xu; Rui Chai; Hongxuan Wang (Environmental Science and Pollution Research, 2022)

Assessment of potential sediment disasters and resilience management of mountain roads using environmental indicators - Chao-Yuan Lin; Yuan-Chung Lai; Shao-Wei Wu; Fan-Chung Mo; Cheng-Yu Lin (Natural Hazards, 2022)
In recent years, extreme rainfall events occur frequently, causing serious watershed sediment disasters, destroying mountain roads, and endangering the safety of residents' lives and property. This study aims to deal with the spatial change of potential sediment movement on the road slope pre-disaster and to screen disaster hot spots for early warning and control system. The conceptual model is used to simulate the distribution of primary and/or derived disasters on a watershed scale to assess the impact of sediment disasters caused by heavy rain event. Correlation analysis shows that the models in assessment of primary disaster and derived disaster are significantly correlated with the collapse ratio and disaster ratio, respectively. Since the primary disaster has been considered when calculating the derived disaster risk, the terrain subdivision along Provincial Highway 21 (Tai-21) is extracted to understand the derived sediment disaster on the road slope. The model can effectively evaluate the road sections prone to disasters. According to the risk level, the hot spot of road slope disasters and the management of disaster resilience are determined and can be the reference for disaster prevention and control.

Phylogeny and conservation of plant U2A/U2A’, a core splicing component in U2 spliceosomal complex - Yue Liu; Yuan Tian; Lan-Xiang Wang; Tao Fan; Jianhua Zhang; Mo-Xian Chen; Ying-Gao Liu (Planta, 2022)

Biochar derived from chicken manure as a green adsorbent for naphthalene removal - Chenchen Liu; Zhihong Yin; Dan Hu; Fan Mo; Ruoyu Chu; Liandong Zhu; Chaozhen Hu (Environmental Science and Pollution Research, 2021)

Deep Placement of Nitrogen Fertilizer Affects Grain Yield, Nitrogen Recovery Efficiency, and Root Characteristics in Direct-Seeded Rice in South China - Yunyan Chen; Pingshan Fan; Zhaowen Mo; Leilei Kong; Hua Tian; Meiyang Duan; Lin Li; Liji Wu; Zaimang Wang; Xiangru Tang; Shenggang Pan (Journal of Plant Growth Regulation, 2021)

Straw Incorporation Coupled with Deep Placement of Nitrogen Fertilizer Improved Grain Yield and Nitrogen Use Efficiency in Direct-Seeded Rice - Yunyan Chen; Pingshan Fan; Lin Li; Hua Tian; Umair Ashraf; Zhaowen Mo; Meiyang Duan; Qiantong Wu; Zheng Zhang; Xiangru Tang; Shenggang Pan (Journal of Soil Science and Plant Nutrition, 2020)

Fasudil attenuates glial cell-mediated neuroinflammation via ERK1/2 and AKT signaling pathways after optic nerve crush - Wei Huang; Qianqian Lan; Li Jiang; Wenya Yan; Fen Tang; Chaolan Shen; Hui Huang; Haibin Zhong; Jian Lv; Siming Zeng; Min Li; Zhongxiang Mo; et al. (Molecular Biology Reports, 2020)

Whether the carbon emission from green roofs can be effectively mitigated by recycling waste building material as green roof substrate during five-year operation? - Liangqian Fan; Jingting Wang; Xiaoling Liu; Hongbing Luo; Ke Zhang; Xiaoying Fu; Mei Li; Xiaoting Li; Bing Jiang; Jia Chen; Shuzhi Fu; You Mo; et al. (Environmental Science and Pollution Research, 2020)

Overexpression of the mango MiCO gene delayed flowering time in transgenic Arabidopsis - Yuan Liu; Cong Luo; Xiu-Juan Zhang; Xin-Xi Lu; Hai-Xia Yu; Xiao-Jie Xie; Zhi-Yi Fan; Xiao Mo; Xin-Hua He (Plant Cell, Tissue and Organ Culture (PCTOC), 2020)

Effect of nitrogen and phosphorus addition on litter decomposition and nutrients release in a tropical forest - Jingfan Zhang; Jian Li; Yingxu Fan; Qifeng Mo; Yingwen Li; Yongxing Li; Zhian Li; Faming Wang (Plant and Soil, 2020)

Effects of silver(I) toxicity on microstructure, biochemical activities, and genic material of Lemna minor L. with special reference to application of bioindicator - Haibo Li; Fan Mo; Yinghua Li; Mingshuai Wang; Zhe Li; Haiyang Hu; Wenhe Deng; Ran Zhang (Environmental Science and Pollution Research, 2020)

Study on the C0–Cw relationship of clay-bearing sandstones based on digital cores - Yufei Fan; Baozhi Pan; Xiuwen Mo; Yuhang Guo; Jian Lei (Acta Geophysica, 2020)

A cytokinin-activation enzyme-like gene improves grain yield under various field conditions in rice - Changgui Wang; Guokui Wang; Yang Gao; Guihua Lu; Jeffrey E. Habben; Guanfan Mao; Guangwu Chen; Jiantao Wang; Fan Yang; Xiaoqiang Zhao; Jing Zhang; Hua Mo; et al. (Plant Molecular Biology, 2020)

ABA and sucrose co-regulate strawberry fruit ripening and show inhibition of glycolysis - Ya Luo; Cong Ge; Yajie Ling; Fan Mo; Min Yang; Leiyu Jiang; Qing Chen; Yuanxiu Lin; Bo Sun; Yong Zhang; Yan Wang; Mengyao Li; et al. (Molecular Genetics and Genomics, 2020)

Compound C attenuates NLRP3 inflammasome despite AMPK knockdown in LPS plus palmitate-induced THP-1 cells - Yuxing Liu; Honghui He; Liangliang Fan; Jingjing Yuan; Hao Huang; Wenjun Yang; Linghao Wang; Zhaohui Mo; Fang Wang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2020)

Acetone adsorption capacity of sulfur-doped microporous activated carbons prepared from polythiophene - Junchao Zhu; Ruofei Chen; Zheng Zeng; Changqing Su; Ke Zhou; Yamian Mo; Yang Guo; Fan Zhou; Jie Gao; Liqing Li (Environmental Science and Pollution Research, 2019)

A multi-risk assessment framework for agricultural land use optimization - Haojie Cui; Ping Guo; Mo Li; Shanshan Guo; Fan Zhang (Stochastic Environmental Research and Risk Assessment, 2019)

Geraniin promotes osteogenic differentiation of bone marrow mesenchymal stem cells (BMSCs) via activating β-catenin: a comparative study between BMSCs from normal and osteoporotic rats - Jiao Mo; Renhua Yang; Fan Li; Bo He; Xiaochao Zhang; Yuqin Zhao; Zhiqiang Shen; Peng Chen (Journal of Natural Medicines, 2019)

Species Diversity and Functional Prediction of Surface Bacterial Communities on Aging Flue-Cured Tobaccos - Fan Wang; Hongwei Zhao; Haiying Xiang; Lijun Wu; Xiao Men; Chang Qi; Guoqiang Chen; Haibo Zhang; Yi Wang; Mo Xian (Current Microbiology, 2018)

Recombinant rabies virus expressing interleukin-6 enhances the immune response in mouse brain - Jun Luo; Boyue Zhang; Yuting Wu; Qin Tian; Meijun Mo; Teng Long; Mingzhu Mei; Ruqi Fan; Ziyu Lyu; He Jiang; Fan Wu; Yingyi Lin; et al. (Archives of Virology, 2018)

Multiple correlation analyses revealed complex relationship between DNA methylation and mRNA expression in human peripheral blood mononuclear cells - Fang-Fei Xie; Fei-Yan Deng; Long-Fei Wu; Xing-Bo Mo; Hong Zhu; Jian Wu; Yu-Fan Guo; Ke-Qin Zeng; Ming-Jun Wang; Xiao-Wei Zhu; Wei Xia; Lan Wang; et al. (Functional & Integrative Genomics, 2018)

A Lower Limb-Pelvis Finite Element Model with 3D Active Muscles - Fuhao Mo; Fan Li; Michel Behr; Zhi Xiao; Guanjun Zhang; Xianping Du (Annals of Biomedical Engineering, 2018)

Using remote sensing information to estimate snow hazard and extreme snow load in China - H. M. Mo; H. P. Hong; F. Fan (Natural Hazards, 2017)

Isolation, identification and pathogenicity of Vibrio harveyi , the causal agent of skin ulcer disease in juvenile hybrid groupers Epinephelus fuscoguttatus × Epinephelus lanceolatus - G M Shen; C Y Shi; C Fan; D Jia; S Q Wang; G S Xie; G Y Li; Z L Mo; J Huang (Journal of Fish Diseases, 2017)
The hybrid grouper, Epinephelus fuscoguttatus (♀) × Epinephelus lanceolatus (♂), is a newly bred cultivated marine fish species of high economic value. However, a skin ulcer disease with high mortality has occurred, and the responsible pathogen remains unknown. In this study, we summarized the epidemic status and external signs of this disease. We screened potential pathogens and finally isolated one bacterial strain ML 01 from affected fish. We subjected healthy juvenile hybrid groupers to bacterial challenge tests with the isolate by immersion, immersion after dermal abrasion and intraperitoneal injection, respectively. Within 14 days post‐infection, the isolate ML 01 caused mass mortality of juveniles infected via immersion after dermal abrasion or intraperitoneal injection. Diseased juveniles displayed obvious signs of skin ulcers. The median lethal dose of ML 01 by intraperitoneal injection was 1.10 × 10 5 colony‐forming units. ML 01 was identified as Vibrio harveyi by bacterial morphology, analytical profile index identification, 16S rDNA sequencing and multilocus sequence analysis. Antibiotic susceptibility tests showed that ML 01 was sensitive to ceftriaxone, doxycycline and minocycline. The results of this study suggest that V. harveyi is the causal agent of skin ulcer disease in juvenile hybrid groupers, thus providing a basis for effective control and prevention of this disease.

Interactions between selenite and different forms of antimony and their effects on root morphology of paddy rice - Qianhua Wu; Renwei Feng; Junkang Guo; Ruigang Wang; Yingming Xu; Zhilian Fan; Liangyu Mo (Plant and Soil, 2017)

Integrative multi-omics analysis revealed SNP-lncRNA-mRNA (SLM) networks in human peripheral blood mononuclear cells - Wei Xia; Xiao-Wei Zhu; Xin-Bo Mo; Long-Fei Wu; Jian Wu; Yu-Fan Guo; Ke-Qin Zeng; Ming-Jun Wang; Xiang Lin; Ying-Hua Qiu; Lan Wang; Pei He; et al. (Human Genetics, 2017)

A novel thymidine phosphorylase mutation in a Chinese MNGIE patient - Hui-Fang Wang; Juan Wang; Yan-Ling Wang; Jian-Jian Fan; Gui-Lin Mo; Feng-Yin Gong; Zhi-Ming Chai; Jin Zhang; Hua-Xing Meng; Chang-Xin Li; Jun-Hong Guo; Chuan-Qiang Pu (Acta Neurologica Belgica, 2017)

Extreme snow hazard and ground snow load for China - H. M. Mo; L. Y. Dai; F. Fan; T. Che; H. P. Hong (Natural Hazards, 2016)

Robust brain parcellation using sparse representation on resting-state fMRI - Yu Zhang; Svenja Caspers; Lingzhong Fan; Yong Fan; Ming Song; Cirong Liu; Yin Mo; Christian Roski; Simon Eickhoff; Katrin Amunts; Tianzi Jiang (Brain Structure and Function, 2015)

Duration-dependent regulation of autophagy by isoflurane exposure in aged rats - Zheng-Qian Li; Lun-Xu Li; Na Mo; Yi-Yun Cao; Bolati Kuerban; Yao-Xian Liang; Dong-Sheng Fan; De-Hua Chui; Xiang-Yang Guo (Neuroscience Bulletin, 2015)

Snow hazard estimation and mapping for a province in northeast China - H. M. Mo; F. Fan; H. P. Hong (Natural Hazards, 2015)

Spatial distribution of heavy metal contamination in soils near a primitive e-waste recycling site - Sheng-Xiang Quan; Bo Yan; Fan Yang; Ning Li; Xian-Ming Xiao; Jia-Mo Fu (Environmental Science and Pollution Research, 2015)

CXXC5 regulates differentiation of C2C12 myoblasts into myocytes - Guangming Li; Xiangli Ye; Xiyang Peng; Yun Deng; Wuzhou Yuan; Yongqing Li; Xiaoyang Mo; Xijun Wang; Yongqi Wan; Xianchu Liu; Tingfang Chen; Zhigang Jiang; et al. (Journal of Muscle Research and Cell Motility, 2014)

MicroRNAs Expression and Function in Cerebral Ischemia Reperfusion Injury - Yu Di; Yang Lei; Feng Yu; Fan Changfeng; Wang Song; Mo Xuming (Journal of Molecular Neuroscience, 2014)

Ranging behavior of eastern hoolock gibbon (Hoolock leuconedys) in a northern montane forest in Gaoligongshan, Yunnan, China - Dao Zhang; Han-Lan Fei; Sheng-Dong Yuan; Wen-Mo Sun; Qing-Yong Ni; Liang-Wei Cui; Peng-Fei Fan (Primates, 2014)

Expression and identification of a novel gene Spata34 in mouse spermatogenic cells - Tingfang Chen; Zhigang Jiang; Wei Xu; Yuequn Wang; Yongqing Li; Yongqi Wan; Wuzhou Yuan; Xiaoyang Mo; Xiushan Wu; Yun Deng; Xiongwei Fan; Dongsong Nie (Molecular Biology Reports, 2014)

Co-remediation of DDT-contaminated soil using white rot fungi and laccase extract from white rot fungi - Biao Fan; Yuechun Zhao; Ganhui Mo; Weijuan Ma; Junqin Wu (Journal of Soils and Sediments, 2013)

Lack of association between IL-23R gene polymorphisms and systemic lupus erythematosus in a Chinese population - Gui-Mei Chen; Chen-Chen Feng; Qian-Ling Ye; Juan Wang; Han Cen; Rui Li; Hui Peng; Mo Zhou; Rui-Xue Leng; Yin-Guang Fan; Jin-Hui Tao; Hai-Feng Pan; et al. (Inflammation Research, 2013)

Continuous evolution of avian infectious bronchitis virus resulting in different variants co-circulating in southern China - Meng Li; Mei-Lan Mo; Bai-Cheng Huang; Wen-Sheng Fan; Zheng-Ji Wei; Tian-Chao Wei; Kang-Ran Li; Ping Wei (Archives of Virology, 2013)

Identification of non-TAL effectors in Xanthomonas oryzae pv. oryzae Chinese strain 13751 and analysis of their role in the bacterial virulence - Shuai Zhao; Wei-Lan Mo; Fan Wu; Wei Tang; Ji-Liang Tang; Boris Szurek; Valérie Verdier; Ralf Koebnik; Jia-Xun Feng (World Journal of Microbiology and Biotechnology, 2013)

Overexpression of a histone H3K4 demethylase, JMJ15, accelerates flowering time in Arabidopsis - Hongchun Yang; Huixian Mo; Di Fan; Ying Cao; Sujuan Cui; Ligeng Ma (Plant Cell Reports, 2012)

Re-expression of miR-21 contributes to migration and invasion by inducing epithelial-mesenchymal transition consistent with cancer stem cell characteristics in MCF-7 cells - Mingli Han; Manran Liu; Yimeng Wang; Zhiqiang Mo; Xiaokai Bi; Zhirong Liu; Yuanming Fan; Xin Chen; Chengyi Wu (Molecular and Cellular Biochemistry, 2012)

Profiling Gene Expression During Gland Morphogenesis of a Glanded and a Glandless Upland Cotton - Ying-Fan Cai; Min Chen; Quan Sun; Yong-Fang Xie; Sheng-Wei Li; Ming-Feng Jiang; Jian-Chuan Mo; You-Lu Yuan; Yu-Zhen Shi; Huai-Zhong Jiang; Zheng Pan; Yun-Ling Gao; et al. (Journal of Plant Biology, 2009)

BREVIS RADIX is involved in cytokinin-mediated inhibition of lateral root initiation in Arabidopsis - Jing Li; Xiaorong Mo; Jirong Wang; Nannan Chen; Huan Fan; Chunyan Dai; Ping Wu (Planta, 2009)

ZNF418, a novel human KRAB/C2H2 zinc finger protein, suppresses MAPK signaling pathway - Yongqing Li; Dan Yang; Yan Bai; Xiaoyang Mo; Wen Huang; Wuzhou Yuan; Zhaochu Yin; Yun Deng; Oleg Murashko; Yuequn Wang; Xiongwei Fan; Chuanbing Zhu; et al. (Molecular and Cellular Biochemistry, 2008)